PR Current Controllers for Harmonics Generators to Test an Inductive Current Transformer - Phung, Anh-Tuan; Vu, Hoang Phuong; Vu, Thuy-Nguyen (Old Journal, 2019)
Current transformers are commonly used electrical devices to measure the current of electric loads. To assess the quality and accuracy of the current transformer, one of the necessary requirements is to evaluate the accuracy of this object under the condition that the primary current has a large distorted waveform and is composed of harmonics. This has led to the need to create a programmable current source capable of generating current that contains basic harmonic components and high harmonics according to present standards. The current source must accurately generate the desired amplitude and frequency values, which in turn requires the use of resonant modulation regulators. The parameters of the regulator greatly affect the quality of the above current source. Therefore, this article will present a method of calculating the proportional-resonant regulator parameter, corresponding to each generated harmonic component. Simulation results performed in MATLAB software have proven effective design methods when applying the generated harmonic components. Experiment results will be discussed in detail for such an advanced regulator.